Developing Knowledge and Theory in the Field of Adult Education: Research Conferences in the 1960’s - Catherine A Hansman; Amy D Rose (Adult Education Research Conference, 2017)
This historical study examines the role of research and the development of adult education research conferences, including the eventual founding and establishment of the Adult Education Research Conference (AERC).
Keywords: AERC; CPAE; Developing Field; Research